Caracterización de los modelos de análisis del riesgo asociado al movimiento repetitivo dentro de los estudios ergonómicos (2022)
The present monograph aimed to characterize the OCRA and JSI analysis models of the risk associated with repetitive movement within ergonomic studies, to identify their applicability, frequency of their or employability in research, their limitations, advantages and disadvantages in order to present a clear perspective regarding the importance of the use of each method within ergonomic risk diagnoses. For this, a descriptive research was carried out, using as information collection instruments the bibliographic analysis, the bibliographic nuance and the content analysis matrix, taking as a sample 20 documents and articles on the research variables. As a result, it was possible to identify that the method most used in research at the national level is the JSI and the international OCRA, the first being much simpler and more reliable, and the second much more difficult to implement. However, unless the technical actions are very uniform in terms of effort and other characteristics such as frequency and duration, OCRA may be preferable.